Factors Associated With the Incidence of Hypertension on Elderly In Kandai Public Health Center, Kendari - Muhammad Ilham; Narmawan Narmawan; Tahiruddin Tahiruddin (KLASICS, 2021)
Abstract. Hypertension is a circulatory system disorder that causes an increase in blood pressure above normal. The tendency of people to live a dynamic lifestyle, consume instant food, consume high-fat food, smoke, and consume alcoholic beverages is very influential on health. This study aimed to determine the factors associated with the incidence of hypertension in the elderly at the Kandai Health Center in Kendari. The design used in this study was a descriptive-analytic study with a cross-sectional design. This study was carried out at the Kandai Health Center in Kendari for 47 respondents taken by accidental sampling. Analysis of the data used in this research was Chi-Square Test analysis. The results showed there was an association between smoking habits and the incidence of hypertension in the elderly (p = 0.011 <0.05), there was an association between salt consumption and the incidence of hypertension in the elderly (p = 0.014 <0.05) and there was an association between alcohol consumption and the incidence of hypertension in the elderly ( p = 0.020 <from α = 0.05). Conclusions in this study are smoking habits, salt consumption and alcohol consumption associated with the incidence of elderly hypertension. Suggestions in this study are for the parties of the Kandai Health Center, Kendari to improve services to the elderly through posbindu so that they can be controlled from non-communicable diseases suffered by the elderly.